Comparison of an effective working hour and harvesting cost between manual harvesting (chisel and sickle) and mechanised harvesting (CKAT and motorised cutter) in oil palm plantation. - Aliuddin Bakar, Muhammad; Firdaus Abdul Rashid, Nur; Syahlan, Syahrizan (International Journal of Engineering and Technology, 2018)
From this paper, it is an effort to investigate the most efficient harvesting tools that must be applied by all oil palm producers. It is similar to identify which harvesting tools are the most efficient that reflected the labour productivity and cost management for harvesting operation. The motorised cutter, mechanised CKAT, manual chisel and manual sickle were tested based on capacity and cost involved. EFC for motorised is superior to manual with 0.29 ha per hour for motorised and 0.22 ha per hour for manual. The trials carried out on manual harvesting technique by using chisel shows that effective working hour per hectare is 1.64 ha per hour and effective working hour per hectare for mechanised harvesting technique is 1.84 ha per hour. Also, the cost involved in both harvesting tools, the motorised cutter price is RM 4500 plus its operational costs, the harvesting cost comes to RM 8.78 per tonne, and for the manual sickle cost is RM 143 plus its operating cost, it comes to RM 10.14 per tonne. Furthermore, the cost for manual chisel is RM 80 and the cost per tonne for manual harvesting technique is RM 22.35 and cost for CKAT is RM1500 plus and cost per tonne for CKAT is RM 24.05. Therefore, by using the motorised cutter, the estate would reduce 50% of its labour requirement in the harvesting operation.Â Â